Effects of nurse presence on perception of feeling of security among adult patients - Ramos, Rita Cui.
This study was conducted to determine the effects of nurse presence as an intervention on the perception of feeling of security among adult patients, and to determine the relationship between the perception of feeling of security with nurse factors and patient factors.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Nurse and patient; Nursing Care; Security (Feeling of).